The popular culture of Shakespeare, Spenser, and Jonson - Lamb, Mary Ellen, 1946- (Routledge studies in Renaissance literature and culture, 2006)
"Focusing on Shakespeare's A Midsummer Night's Dream and The Merry Wives of Windsor, Spenser's The Faerie Queene, and Jonson's Oberon, The Fairy Prince and The Sad Shepherd, Mary Ellen Lamb explores the ways in which early modern literature formed a particularly productive site of contest for deep social changes, and how these changes in turn played a large role in shaping some of the most well-known works of the period." "This book breaks new ground by considering productions of popular culture from above, rather than from below. Drawing from theorists of cultural studies, such as Pierre Bourdieu, Roger Chartier, and John Friske, this project synthesizes work from disparate fields to provide new readings of well-known literary works. It will be of particular interest to literary scholars, to cultural and social historians, and to general readers interested in fairies, old wives' tales and hobby-horses."--Jacket.